Arius’ Christology and the Question of Redemption - Markus Schmidt (Proceedings of The International Conference on Theology, Religion, Culture, and Humanities, 2025)
The Ancient Church celebrated the Council of Nicaea in 325. The main reason was to address the Christology of the presbyter Arius of Alexandria (Egypt), who promoted his unorthodox ideas about Jesus of Nazareth in view of his pastoral work. His Christological teachings became widespread and influenced faithful and clerics. As a result, they threatened the apostolic faith of the Church. Arius teaches that the Son of God cannot be God in the full sense of the word. He differs from the Father because he is not eternal or co-eternal and does not have his being with the Father. The Son did not exist before his generation, but was begotten before all things. Arius, thus, emphasizes God as a monad and the source of all beings. Therefore, the soteriological question arises how Jesus Christ can be the redeemer if he is not God. Arius' Christological concept cannot answer this question because in this view, Christ, without being God, cannot work out redeeming humanity. What needs redeeming is the human sin against God. For that, one must bridge the absolute abyss between God and humanity, but a human being cannot cross that boundary between God and humanity. Only God, as God, can perform this redemption, but for Arius, Jesus Christ is not God in the full sense of the word. Because of that, the Jesus Christ of Arius' teachings cannot save humanity. As a result, the soteriological consequence of Arius' Christology is tragic: because Christ is not God, he cannot be the redeemer. He cannot bridge the abyss between God and humanity. Thus, there is no way that human beings can win reconciliation with God because Jesus Christ is not the Messiah. Humanity will remain in its sinful state.